(untitled) (Al Fiddhoh: Journal of Banking, Insurance, and Finance, 2022)
This study aims to to know recording and our financial report conducted by small and medium businesses UMKM ladu arai pinang gusti, to see how recording and our financial report small and medium businesses UMKM ladu arai pinang gusti that is in accordance with the accounting standard entity micro small and medium enterprises ( SAK EMKM ). The qualitative method was used in the study with the approach descriptive, researchers used 2 the kind of data that is primary and secondary data. Researchers used in this research stage 4 which are (1) data collection , of the stages this researchers used interview techniques, observation and also documentation (2) reduction data (3) presentation of data (4) towing conclusion. The results of the study showed that the registration of a financial report done by the owners of the small and medium businesses umkm ladu arai pinang gusti use and very modest, the reason why small and medium businesses umkm in village records not financial report in accordance with SAK EMKM is the owner did not understand SAK EMKM and how preparing financial reports that is in accordance with the accounting standard entity micro small and medium enterprises (SAK EMKM).